Flexible perovskite solar cell with excellent bending performance and preparation method thereof

By introducing a 3-methacryloyloxypropyltrimethoxysilane buffer layer between the perovskite and hole transport layers, a two-step spin-coating deposition method was used to prepare flexible perovskite solar cells. This solved the problem of cracking of flexible films during bending, improved the stability and photovoltaic performance of the cells, and reduced production costs.

CN121038499APending Publication Date: 2025-11-28SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511186507.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-24
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing flexible thin-film perovskite solar cells are prone to cracking during bending, leading to degradation of photoelectric performance and poor stability, making it difficult to meet the requirements for long-term use.

Method used

3-Methacryloyloxypropyltrimethoxysilane was introduced as a buffer layer between the perovskite and the hole transport layer, and a two-step spin-coating deposition method was used to prepare flexible perovskite solar cells, thereby improving their bending resistance and stability.

Benefits of technology

It significantly improves the long-term stability and bending stability of flexible perovskite solar cells, enhances photovoltaic performance, reduces production costs, and simplifies the fabrication process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005562391400000051
    Figure BDA0005562391400000051
  • Figure HDA0005562391410000011
    Figure HDA0005562391410000011
  • Figure HDA0005562391410000012
    Figure HDA0005562391410000012
Patent Text Reader

Abstract

The invention provides a flexible perovskite solar cell with excellent bending performance and a preparation method thereof. 3-methacryloyloxypropyltrimethoxysilane (KH570), formamidine iodide, methylamine bromide, methyl ammonium chloride, spiroOMeTAD, a lithium salt acetonitrile solution and tBP chlorobenzene (CB) are used as raw materials, a perovskite thin film is prepared through a two-step spin-coating deposition method, and a silver electrode is prepared through a thermal evaporation method. The bending resistance of the prepared flexible perovskite solar cell (f-PSCs) is remarkably improved, the performance retention rate is improved from 53% to 90% after 3000 times of bending cycles, and the average photoelectric conversion efficiency of the cell is improved from 18.72% to 21.42%. According to the invention, a new way is opened up for improving the photovoltaic performance and bending resistance of f-PSCs by using the silane oxide coupling agent, and an important technical reference is provided for realizing industrialization of flexible perovskite solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a flexible perovskite solar cell with excellent bending performance and its preparation method, which belongs to the field of energy technology. Background Technology

[0002] With the continuous development of society, non-fossil energy is an inevitable choice for coordinating the low-carbon transition of energy and ensuring energy security. Therefore, finding alternative new energy sources has become a primary issue for the development of countries around the world. In the current field of new energy, solar energy, with its advantages of wide distribution, large total volume, no pollution, and sustainability, has become one of the most promising future energy sources. Against this backdrop, solar photovoltaic power generation has become a rapidly developing renewable energy technology in recent decades.

[0003] Flexible thin-film perovskite solar cells (f-PSCs) are fabricated on lightweight, bendable thin-film substrates. Compared to traditional silicon solar cells, flexible perovskite devices offer advantages such as high efficiency, low cost, and simple manufacturing processes, making them one of the most competitive products in the photovoltaic industry.

[0004] Currently, polymer substrates are primarily used for fabricating flexible devices. However, when the bending radius of the polymer substrate reaches a certain value, the transparent conductive layer breaks, leading to a severe degradation in photoelectric performance. Simultaneously, water molecules easily pass through the polymer substrate, affecting the mechanical properties and stability of perovskite devices. Furthermore, the stress or deformation within the flexible substrate after low-temperature treatment inevitably increases defects. Therefore, the short-circuit current (J / s) of f-PSCs... sc ), open circuit voltage (V) oc The fill factor (FF) and flexural strength of f-PSCs are typically lower than those of similar devices on conductive glass substrates. To improve battery stability and reduce performance degradation, the fabrication of f-PSCs with bending resistance has become a current research focus.

[0005] To achieve long-term stability of solar cells, researchers have developed numerous methods, such as composite material engineering, defect passivation, and interface engineering. Existing studies have shown that silicone resins possess excellent self-healing and adhesion properties, which can significantly improve the power conversion efficiency (PCE), bending resistance, and long-term stability of f-PSCs. This invention introduces 3-methacryloyloxypropyltrimethoxysilane (KH570) between the perovskite and hole transport layers, resulting in a significant improvement in the bending resistance of flexible perovskite solar cells. This opens up a new avenue for improving the photovoltaic performance and bending resistance of f-PSCs using silane coupling agents, and has great application potential. Summary of the Invention

[0006] The purpose of this invention is to fabricate flexible perovskite solar cells with excellent bending resistance. 3-Methacryloxypropyltrimethoxysilane (KH570) is used as a buffer layer between the perovskite and hole transport layer to reduce cracking of f-PSCs during bending, thereby improving their long-term stability and bending stability.

[0007] Another objective of this invention is to provide a method for preparing flexible perovskite solar cells using a two-step spin-coating deposition method. This method has low production costs, high production efficiency, is environmentally friendly, and uses simple equipment, making it more conducive to actual production and providing an important reference for the industrialization of batteries.

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] A method for fabricating flexible perovskite solar cells using 3-methacryloyloxypropyltrimethoxysilane is introduced, comprising the following steps:

[0010] 1. Spin-coating a SnO2 electron transport layer onto the substrate

[0011] First, the PEN / ITO substrate was directly cleaned with anhydrous ethanol. The SnO2 colloid was diluted with deionized water (SnO2 / H2O volume ratio 1:3) and stirred for 50 minutes to prepare a SnO2 solution. The obtained SnO2 solution was spin-coated onto the PEN / ITO substrate at 3000 rpm for 30 seconds, and then annealed at 100°C for 50 minutes. Finally, the spin-coated surface was treated with a UV lamp under an ozone atmosphere for 15 minutes. After cooling, a two-step method was used to prepare the perovskite layer.

[0012] 2. Two-step method for preparing perovskite layers

[0013] (1) Preparation of perovskite layer by two-step process: First, the three drugs lead iodide, cesium iodide and lead chloride are dissolved in a mixture of dimethylformamide and dimethyl sulfoxide (dimethylformamide: dimethyl sulfoxide = 9:1), and then placed on a heating table at 70°C and heated and stirred for 12 hours.

[0014] (2) Dissolve formamidine iodide, methylamine bromide, and methylammonium chloride in 1 ml of isopropanol at a molar ratio of (10:1:1) and stir at room temperature for 13 hours to prepare a perovskite precursor solution. Then take an appropriate amount of lead iodide mixed solution and spin-coat it onto the SnO2 surface at 1500 rpm for 30 s, and then anneal it at 70 °C for 14 s.

[0015] (3) After the lead iodide is prepared, the prepared formamidine iodide mixed solution is spin-coated onto the lead iodide film at 1500 rpm for 30 s, and then immediately annealed at 130℃ for 45 min. At this point, the perovskite prepared by the two-step method is complete.

[0016] 3. Introduction of 3-methacryloyloxypropyltrimethoxysilane

[0017] 3-Methacryloxypropyltrimethoxysilane was spin-coated onto a PEN / ITO / SnO2 / perovskite substrate at 1500 rpm for 30 s, and then annealed at 100 °C for 5 min. Subsequently, a spiro-OMeTAD precursor solution was prepared by dissolving spiro-OMeTAD, lithium salt acetonitrile solution, and tBP in chlorobenzene (CB), and then spin-coated onto the perovskite film at 4000 rpm for 30 s.

[0018] 4. Deposited silver electrode

[0019] To complete the fabrication of flexible PSCs, silver electrodes were prepared using a thermal evaporation method.

[0020] Finally, the photoelectric performance of the battery was characterized, and the photoelectric conversion performance and bending resistance of the battery were tested.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] This invention provides a flexible perovskite solar cell with excellent bending performance and its preparation method. It introduces 3-methacryloyloxypropyltrimethoxysilane to prepare flexible perovskite solar cells, which reduces cracking of flexible perovskite solar cells during bending, thereby significantly improving their long-term stability and bending stability.

[0023] This invention also provides a method for preparing flexible perovskite solar cells using a two-step spin-coating deposition process, which enables the perovskite layer to be uniformly distributed on the substrate, resulting in a more uniform film formation. This method features low production cost, high production efficiency, environmental friendliness, and simple equipment, making it more suitable for practical production and providing an important reference for the industrialization of solar cells. Attached Figure Description

[0024] Appendix Figure 1 XRD patterns of perovskite films (modified with 3-methacryloxypropyltrimethoxysilane and control group);

[0025] Appendix Figure 2 SEM images of perovskite films (modified with 3-methacryloxypropyltrimethoxysilane and control group);

[0026] Appendix Figure 3 JV curves of flexible perovskite solar cells (modified with 3-methacryloxypropyltrimethoxysilane and control group) in different scanning directions;

[0027] Appendix Figure 4Results of mechanical bending changes in flexible perovskite solar cells (modified with 3-methacryloyloxypropyltrimethoxysilane and control group);

[0028] Appendix Figure 5 SEM images of flexible perovskite solar cells (modified with 3-methacryloxypropyltrimethoxysilane and control group) after 3000 bending cycles. Detailed Implementation

[0029] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0030] I. Fabrication of Flexible Perovskite Solar Cells Introduced with 3-Methacryloyloxypropyltrimethoxysilane

[0031] First, the PEN / ITO substrate was directly cleaned with anhydrous ethanol. SnO2 colloid was diluted with deionized water (SnO2 / H2O volume ratio 1:3) and stirred for 50 min to prepare a SnO2 solution. The obtained SnO2 solution was spin-coated onto the PEN / ITO substrate at 3000 rpm for 30 s, and then annealed at 100 °C for 50 min. Finally, the spin-coated surface was treated with a UV lamp under an ozone atmosphere for 15 min. After cooling, a two-step preparation method was performed. The perovskite layer was prepared using a two-step process: First, lead iodide, cesium iodide, and lead chloride were dissolved in a mixed solvent of dimethylformamide and dimethyl sulfoxide (dimethylformamide: dimethyl sulfoxide = 9:1) at mass ratios of 600 mg, 16.9 mg, and 9 mg, respectively. Then, the solution was placed on a heating stage at 70 °C and heated with stirring for 12 hours. A perovskite precursor solution was prepared by dissolving formamidine iodide, methylamine bromide, and methylammonium chloride in a ratio of 60 mg:6 mg:6 mg in 1 ml of isopropanol and stirring at room temperature for 13 hours. Then, a suitable amount of a mixed solution of lead iodide, cesium iodide, and lead chloride was spin-coated onto a SnO2 surface at 1500 rpm for 30 seconds, followed by annealing at 70°C for 14 seconds. After the lead iodide film was prepared, a prepared formamidine iodide mixed solution was spin-coated onto the lead iodide film at 1500 rpm for 30 seconds, followed immediately by annealing at 130°C for 45 minutes. This completed the two-step perovskite preparation. Finally, 3-methacryloyloxypropyltrimethoxysilane was spin-coated onto a PEN / ITO / SnO2 / perovskite substrate at 1500 rpm for 30 seconds and annealed at 100°C for 5 minutes. Subsequently, a spiro-OMeTAD precursor solution was prepared by dissolving 72.3 mg of spiro-OMeTAD, 17.5 μL of lithium salt acetonitrile solution (520 mg / mL), and 28.8 μL of tBP in 1 mL of chlorobenzene (CB). This solution was then spin-coated onto a perovskite film at 4000 rpm for 30 s. Finally, a silver electrode was prepared using 99.9% Ag as the raw material via thermal evaporation. The cell size was ultimately controlled to 0.08 cm. 2 .

[0032] Appendix Figure 1 These are X-ray diffraction (XRD) spectra of perovskite films with different concentrations of 3-methacryloxypropyltrimethoxysilane. The figures show that no new peaks appeared in the perovskite films after modification with 3-methacryloxypropyltrimethoxysilane. Furthermore, after treatment with 3 mg / mL... -1The perovskite films modified with 3-methacryloxypropyltrimethoxysilane showed enhanced signals on the (110) and (220) crystal planes of the perovskite, with significantly suppressed lead iodide peaks. This indicates that treatment with 3-methacryloxypropyltrimethoxysilane plays a crucial role in promoting the crystallization of perovskite and facilitates the transformation of lead iodide into the perovskite phase. Simultaneously, a small amount of lead iodide can passivate defects, which is beneficial for improving the quality of the perovskite film. However, excessive lead iodide will inhibit grain boundary growth, leading to grain boundary defects and poor stability. Furthermore, when the concentration of 3-methacryloxypropyltrimethoxysilane is 3 mg / mL... -1 At that time, the highest (220) peak and the lowest lead iodide peak appeared, indicating that 3 mg mL -1 This is the optimal concentration.

[0033] Appendix Figure 2 These are surface SEM images of perovskite films before modification and after modification with 3-methacryloxypropyltrimethoxysilane. It can be seen that the surface morphology of the unmodified perovskite exhibits many small pores. In contrast, the perovskite film modified with 3-methacryloxypropyltrimethoxysilane shows a significant improvement in quality.

[0034] II. Photoelectric Performance Testing of Flexible Perovskite Solar Cells

[0035] At 1000W / m 2 Under high solar radiation, the reliability of the battery's photoelectric performance under working conditions was verified using a solar simulator, electrochemical workstation, computer, and related software.

[0036] (1) JV curve test of flexible perovskite solar cells

[0037] Appendix Figure 3 The JV curves for the perovskite solar cells before and after modification with 3-methacryloxypropyltrimethoxysilane are shown. The solid and dashed lines represent the reverse and forward scan curves, respectively. According to the hysteresis index (HI) calculation method, the HI of the perovskite solar cells is significantly reduced, indicating that modification with 3-methacryloxypropyltrimethoxysilane reduces charge recombination. These results demonstrate that 3-methacryloxypropyltrimethoxysilane can effectively reduce the trapped state density of perovskite thin films, decrease charge loss, and improve the photovoltaic performance of flexible devices. Specific performance parameters of the cells are shown in the table below.

[0038]

[0039] As shown in the table above, the highest PCE of the unmodified perovskite solar cell is 20.28%, and the short-circuit current (J) is... sc The value is 23.58 mA / cm. -2 Open circuit voltage (V)oc The voltage is 1.206V, and the fill factor (FF) is 71.30%, while the highest PCE of the perovskite solar cell modified with 3-methacryloyloxypropyltrimethoxysilane is 23.05%, and the V is even higher. oc 1.223V, J sc 25.13 mA cm -2 The FF was 74.90%. Compared with the control group, the VFF of the perovskite solar cell modified with 3-methacryloyloxypropyltrimethoxysilane was significantly higher. oc The JFF of the perovskite solar cell was significantly improved, mainly due to the reduction in thin film defects and carrier recombination. Furthermore, the JFF of the perovskite solar cell modified with 3-methacryloyloxypropyltrimethoxysilane was significantly improved. sc The improvement is related to appropriate grain size and enhanced charge migration.

[0040] III. Bending Resistance Testing of Flexible Perovskite Solar Cells

[0041] Appendix Figure 4 (a) The mechanical bending changes of the original perovskite solar cell and the 3-methacryloxypropyltrimethoxysilane-modified perovskite solar cell after 1000 bending cycles at different bending radii (r, from 1 to 5 mm). As can be seen from the figure, with the increase of the bending radius, the bending stability of the 3-methacryloxypropyltrimethoxysilane-modified perovskite solar cell is better than that of the control group. The device modified with 3-methacryloxypropyltrimethoxysilane exhibits good bending resistance. Figure 4 (b) shows that after 3000 bending cycles (bending radius 5 mm), it can still retain 90% of its initial value, while the control group only retains 53% of its original efficiency. This is due to the good adhesion properties of 3-methacryloyloxypropyltrimethoxysilane, which enables the perovskite film to bond firmly together during bending.

[0042] Appendix Figure 5 These are scanning electron microscope (SEM) images of the surface morphology of the original perovskite solar cell and the perovskite solar cell modified with 3-methacryloxypropyltrimethoxysilane after 3000 bending cycles. The images clearly show obvious cracks on the surface of the control group, while the perovskite solar cell modified with 3-methacryloxypropyltrimethoxysilane maintained its strength after 3000 bending cycles, showing only minor damage. This further demonstrates that the perovskite solar cell modified with 3-methacryloxypropyltrimethoxysilane has strong bending resistance. The significantly enhanced bending resistance of 3-methacryloxypropyltrimethoxysilane indicates that it is a good modifying material for improving the bending resistance of flexible perovskite solar cells.

[0043] For those skilled in the art, various modifications and improvements can be made to the present invention without departing from its principles, and these modifications and improvements also fall within the protection scope of the present invention.

Claims

1. A flexible perovskite solar cell with excellent bending performance and its fabrication method, mainly comprising: First, the PEN / ITO substrate was directly cleaned with anhydrous ethanol. SnO2 colloid was diluted with deionized water (SnO2 / H2O volume ratio 1:3) and stirred for 50 min to prepare an aqueous SnO2 solution. The obtained SnO2 aqueous solution was spin-coated onto the PEN / ITO substrate at 3000 rpm for 30 s, and then annealed at 100 °C for 50 min. Finally, the spin-coated surface was treated with a UV lamp under an ozone atmosphere for 15 min. After cooling, a two-step preparation method was performed. The perovskite layer was prepared using a two-step process: First, lead iodide, cesium iodide, and lead chloride were dissolved at 600 mg, 16.9 mg, and 9 mg respectively in a mixed solvent of dimethylformamide and dimethyl sulfoxide (dimethylformamide:dimethyl sulfoxide = 9:1), and then placed on a heating stage at 70 °C and heated and stirred for 12 hours. A perovskite precursor solution was prepared by dissolving formamidine iodide, methylamine bromide, and methylammonium chloride in a ratio of 60 mg:6 mg:6 mg in 1 ml of isopropanol and stirring at room temperature for 13 hours. Then, a suitable amount of a mixed solution of PbI2, cesium iodide, and lead chloride was spin-coated onto a SnO2 surface at 1500 rpm for 30 seconds, followed by annealing at 70°C for 14 seconds. After the PbI2 film was prepared, the prepared formamidine iodide mixed solution was spin-coated onto the PbI2 film at 1500 rpm for 30 seconds, followed immediately by annealing at 130°C for 45 minutes. This completed the two-step perovskite preparation. Finally, 3-methacryloyloxypropyltrimethoxysilane (KH570) was spin-coated onto a PEN / ITO / SnO2 / perovskite substrate at 1500 rpm for 30 seconds and annealed at 100°C for 5 minutes. Subsequently, 72.3 mg of spiro-OMeTAD, 17.5 μL of lithium salt acetonitrile solution (520 mg / mL), and 28.8 μL of tBP were dissolved in 1 mL of chlorobenzene (CB) to prepare a spiro-OMeTAD precursor solution, which was then spin-coated onto a perovskite film at 4000 rpm for 30 s. Finally, a silver electrode was prepared using 99.9% Ag as the raw material via thermal evaporation, controlling the cell size to 0.08 cm. 2 .

2. The method for preparing SnO2 according to claim 1, characterized in that, The SnO2:H2O volume ratio in the SnO2 solution used is 1:

3.

3. The SnO2 preparation method according to claim 1, characterized in that, Anneal at 100°C for 50 min, then treat the spin-coated surface with UV lamp under ozone atmosphere for 15 min.

4. The method for preparing lead iodide, cesium iodide, and lead chloride solution according to claim 1, characterized in that, V in a mixture of dimethylformamide and dimethyl sulfoxide 二甲基甲酰胺 :V 二甲基亚砜 =9:

1.

5. The method for preparing lead iodide, cesium iodide, and lead chloride solution according to claim 1, characterized in that, The stirring temperature was 70℃ and the stirring time was 12 hours.

6. The method for preparing lead iodide, cesium iodide, and lead chloride solution according to claim 1, characterized in that, The masses of lead iodide, cesium iodide, and lead chloride are 600 mg, 16.9 mg, and 9 mg, respectively.

7. The method for preparing the formamidine iodide, methylamine bromide, and methylammonium chloride precursor solution according to claim 1, characterized in that, The amounts of formamidinium iodide, methylamine bromide, methylammonium chloride, and isopropanol were 60 mg, 6 mg, 6 mg, and 1 ml, respectively.

8. The method for preparing 3-methacryloyloxypropyltrimethoxysilane according to claim 1, characterized in that, 3-Methacryloxypropyltrimethoxysilane (KH570) was spin-coated onto a PEN / ITO / SnO2 / perovskite substrate at 1500 rpm for 30 s, at a processing temperature of 100 °C for 5 min.

9. The preparation method according to claim 1, characterized in that, When preparing the spiro-OMeTAD precursor solution, the amounts of spiro-OMeTAD, lithium salt acetonitrile solution, tBP, and chlorobenzene (CB) were 72.3 mg, 17.5 μL, 28.8 μL, and 1 ml, respectively.

10. According to the preparation method described in claims 1 to 9, those skilled in the art can make several modifications and improvements to the present invention without departing from the principle of the present invention, and these modifications and improvements also fall within the protection scope of the claims of the present invention.